Intracranial aneurysm distribution and characteristics according to gender. (3rd September 2018) - Krzyżewski, Roger M.; Kliś, Kornelia M.; Kucala, Renata; Polak, Jarosław; Kwinta, Borys M.; Starowicz-Filip, Anna; Stachura, Krzysztof; Piszczek, Karolina; Moskała, Marek; Tomaszewski, Krzysztof A.
Abstract: Objective: Female sex is associated with a greater prevalence of cerebral aneurysms. However, it also might be linked to the location and size of the aneurysm. The aim of this study was to find the link between female sex and aneurysm characteristics. Methods: Our study group consisted of 357 patients admitted to the hospital with both unruptured and ruptured aneurysms confirmed by Digital Subtraction Angiography or Computed Tomography Angiography and aneurysmal subarachnoid haemorrhage confirmed by head CT. Patients' medical records were analyzed for necessary information including, but not limited to medical history, blood test results, and aneurysm prevalence, size and location. Results: Women constituted 232 (64.98%) of all patients. In this group, compared to males, we observed a more common occurrence of multiple aneurysms (1.35 ± 0.67 vs. 1.2 ± 0.57; p = .046) and left internal carotid artery aneurysms (25.88% vs. 13.93%; p < .01). Anterior communicating artery aneurysms were less common (17.11% vs. 31.15%; p < .01). Women also had lower dome-to-neck ratios (2.16 ± 0.82 vs. 2.82 ± 1.92; p < .01), were less likely to be smokers (53.6% vs. 33.19%; p < .01) and smoked fewer cigarettes per day (15.09 ± 6.62 vs. 21.09 ± 11.08; p < 0.01). Conclusions: Female patients have a greater risk of multiple aneurysms and left internal carotid artery aneurysms, but a lower risk of anterior communicating artery aneurysms.